High speed synchrotron X-ray imaging of ultrasonic bubble cloud in liquid metal. (November 2015) - Wang, C; Tang, D; Zhang, W; Du, W; Connolley, T; Mi, J
Abstract: This paper presents the real-time and in-situ synchrotron X-ray high speed imaging studies of ultrasound bubbles and bubble cloud in a liquid Sn-30%Cu alloy. The collective behaviour of the ultrasound bubbles generated by ultrasound powders of 60 W and 100W were successfully captured. The number density of the individual bubbles and the density of the continuous bubble cloud were calculated from the information extracted from the images sequences and presented for the first time for the liquid Sn-30%Cu alloy.